2016
DOI: 10.1093/geront/gnw010
|View full text |Cite
|
Sign up to set email alerts
|

Residential Reasoning and the Tug of the Fourth Age

Abstract: The fourth age is generally conceived as an experience of loss, but it also functions as a social imaginary. Our study suggests that the fourth age, both as a potential personal destiny and a social construct, influences housing decisions among those firmly in the third age. More attention in housing research to prudential anticipation of the fourth age as well as the relational aspects of residential reasoning would enhance understanding of late-life housing choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 33 publications
2
32
1
Order By: Relevance
“…The majority of participants (n = 34) felt negative about ageing, that it was something that happened to them and for which they could not prepare. In contrast to these participants, other studies (Kornadt and Rothermund 2014;Koss and Ekerdt 2016) found that planning and preparatory activities for age-related changes helped and were organized by life domains. These domains differed between preparing for the third age (activities peaking around age 65, focusing on leisure, work, and fitness activities, and appearance) and in preparing for the fourth age (activities continued linearly up to age 80, focusing on independence, housing, and financial issues).…”
Section: The Fourth Agementioning
confidence: 58%
“…The majority of participants (n = 34) felt negative about ageing, that it was something that happened to them and for which they could not prepare. In contrast to these participants, other studies (Kornadt and Rothermund 2014;Koss and Ekerdt 2016) found that planning and preparatory activities for age-related changes helped and were organized by life domains. These domains differed between preparing for the third age (activities peaking around age 65, focusing on leisure, work, and fitness activities, and appearance) and in preparing for the fourth age (activities continued linearly up to age 80, focusing on independence, housing, and financial issues).…”
Section: The Fourth Agementioning
confidence: 58%
“…New social and recreational activities can be planned for these years, also influencing the choice of housing and preferences held. At the same time, as reported by Koss and Eckert (2017), among the third agers, anticipation of the fourth age and the functional loss it may bring can influence the housing preferences of those making housing decisions in the third age.…”
Section: Housing Choice and Residential Reasoning Among Older Peoplementioning
confidence: 71%
“…Housing preferences can be said to change with age, as with the advancement in age more convenient and supportive housing is preferred or found necessary. Such preferences or housing choices can be expressed as residential mobility (Litwak and Longino 1987; Mulder and Hooimeijer 1999) or in the residential reasoning of older people as shown by Granbom (2014) and Koss and Ekerdt (2017), where older people tend to consider future health conditions when discussing future housing choices (Litwak and Longino 1987; Mulder and Hooimeijer 1999).…”
Section: Housing Choice and Residential Reasoning Among Older Peoplementioning
confidence: 99%
“…Researchers distinguish two different categories -"third age" (up to 75 years old) and "fourth age" (Laslett, 1991;Koss & Ekerdt, 2016).…”
Section: Resultsmentioning
confidence: 99%